2018
DOI: 10.1111/imm.12894
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible transcription factors, HIF1A and HIF2A, increase in aging mucosal tissues

Abstract: Hypoxia (i.e. oxygen deprivation) activates the hypoxia-signalling pathway, primarily via hypoxia-inducible transcription factors (HIF) for numerous target genes, which mediate angiogenesis, metabolism and coagulation, among other processes to try to replenish tissues with blood and oxygen. Hypoxia signalling dysregulation also commonly occurs during chronic inflammation. We sampled gingival tissues from rhesus monkeys (Macaca mulatta; 3-25 years old) and total RNA was isolated for microarray analysis. HIF1A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 83 publications
(161 reference statements)
4
39
1
1
Order By: Relevance
“…Aging is correlated with a reduction of cellular oxygen supply, which is characterized by decreased oxygen supply to tissue, a reduction of tissue PO2, and the activity of several enzymes and metabolic factors [29]. Hif3a (hypoxia-inducible factor 3A gene) has been reported to show significant differences in elderly tissues and is positively correlated with aging [30]. In the present study, we found that Hif3a was significantly upregulated in the model group.…”
Section: Discussionsupporting
confidence: 54%
“…Aging is correlated with a reduction of cellular oxygen supply, which is characterized by decreased oxygen supply to tissue, a reduction of tissue PO2, and the activity of several enzymes and metabolic factors [29]. Hif3a (hypoxia-inducible factor 3A gene) has been reported to show significant differences in elderly tissues and is positively correlated with aging [30]. In the present study, we found that Hif3a was significantly upregulated in the model group.…”
Section: Discussionsupporting
confidence: 54%
“…Besides its role as an essential factor in VEGF-mediated effects on ECs, HIF-1 also has critical cell-autonomous functions in ECs [43,85]. In this regard, HIF participates in the formation of new vessels, enhancing the delivery of oxygenated blood to tissues [63]. In support of this, ECs under hypoxic conditions generate tube formation, which is negatively regulated by melatonin treatment.…”
Section: Hif and Endothelial Cellsmentioning
confidence: 98%
“…Results have reported that the loss of epidermal HIF-1α accelerates epidermal aging and affects re-epithelialization in humans and mice [62]. Notably, significant elevations in both hypoxia-inducible transcription factors HIF-1α and HIF-1β gene expression have also been found in the gingival tissues of aged animals, even though these tissues were deemed clinically healthy [63]. In a model of limb ischemia in mice, HIF-1 was found to mediate angiogenesis and, therefore, has been proposed to contribute to the pathological aging process [54].…”
Section: The Physio-pathological Role Of Hif In Agingmentioning
confidence: 99%
“…These cellular behaviors and response pathways were influenced by the aging process. EMT has been shown to decrease in senescent cells [ 33 ], whereas mTOR [ 34 , 35 ] and hypoxia-related pathways [ 36 , 37 ] have been shown to be induced. Apoptosis and senescence are cellular responses to damage with different mechanisms; both are involved in aging, and their relationship may vary under different conditions [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%